USING PICTURESWITH PICTURE DESCRIBING TECHNIQUE TO IMPROVE THE SPEAKING ACHIEVEMENT - Jaya Nur Iman (Universitas Indo Global Mandiri, 2016)
This research was carried out to see whether or not the independent variable (using pictures with picture describing technique) could give positive impact on the dependent variable (the speaking achievement). The one-group pretest-posttest design was used in this paper. The population of this research was the all second semester undergraduate students of informatics engineering study program of Indo Global Mandiri University in the academic year of 2014/2015. Twenty four students were taken as the sample by using purposive sampling technique. The treatment was given for 12 meetings excluding pretest and posttest. Speaking rubric was used to measure the students’ speaking achievement. The findings showed that (1) there was a positive impact on the students’ speaking achievement after the intervention was given where the t-obtained (9.023) was higher than t-table (2.500) and the Sig.value 0.000 was lower than 0.01. Therefore, it could be concluded that using pictures with picture describing technique could give positive impact on the speaking achievement and it also could be used as the alternative medium of instruction in the teaching and learning environment.Keywords : pictures, picture describing technique, speaking achievement